Fine Mapping of Two Interacting Loci for Transmission Ratio Distortion in Rice (Oryza sativa L.) - Zhang, Chaopu; Wang, Jilin; Xiao, Xiongfeng; Wang, Dianwen; Yuan, Zhiyang; Zhang, Xiaodan; Sun, Wenqiang; Yu, Sibin (Frontiers in Plant Science, 2022)
Transmission ratio distortion (TRD) denotes the observed allelic or genotypic frequency deviation from the expected Mendelian segregation ratios in the offspring of a heterozygote. TRD can severely hamper gene flow between and within rice species. Here, we report the fine mapping and characterization of two loci (TRD4.1 and TRD4.2) for TRD using large F2 segregating populations, which are derived from rice chromosome segment substitution lines, each containing a particular genomic segment introduced from the japonica cultivar Nipponbare (NIP) into the indica cultivar Zhenshan (ZS97). The two loci exhibited a preferential transmission of ZS97 alleles in the derived progeny. Reciprocal crossing experiments using near-isogenic lines harboring three different alleles at TRD4.1 suggest that the gene causes male gametic selection. Moreover, the transmission bias of TRD4.2 was diminished in heterozygotes when they carried homozygous TRD4.1ZS97. This indicates an epistatic interaction between these two loci. TRD4.2 was mapped into a 35-kb region encompassing one candidate gene that is specifically expressed in the reproductive organs in rice. These findings broaden the understanding of the genetic mechanisms of TRD and offer an approach to overcome the barrier of gene flow between the subspecies in rice, thus facilitating rice improvement by introgression breeding.